2015
DOI: 10.1515/hsz-2014-0221
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein antagonist gremlin-1 regulates colon cancer progression

Abstract: Bone morphogenetic proteins (BMP) are phylogenetically conserved signaling molecules of the transforming growth factor-beta (TGF-beta) superfamily of proteins, involved in developmental and (patho)physiological processes, including cancer. BMP signaling has been regarded as tumor-suppressive in colorectal cancer (CRC) by reducing cancer cell proliferation and invasion, and by impairing epithelial-to-mesenchymal transition (EMT). Here, we mined existing proteomic repositories to explore the expression of BMPs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 104 publications
0
50
0
Order By: Relevance
“…Grem1 is overexpressed in carcinomaassociated fibroblasts of several human carcinomas, including colon carcinomas, and promotes tumor cell proliferation (42).…”
Section: Here We Identify Cd34mentioning
confidence: 99%
“…Grem1 is overexpressed in carcinomaassociated fibroblasts of several human carcinomas, including colon carcinomas, and promotes tumor cell proliferation (42).…”
Section: Here We Identify Cd34mentioning
confidence: 99%
“…On the other hand, Van Vlodrop et al (1) reported that methylation of the promoter region of Gremlin was associated with higher tumor grade, higher tumor stage, reduced MVD and shorter survival time in patients with CCRCC. Karagiannis et al (16) showed that GREM1 promotes the loss of cancer cell differentiation at the cancer invasion front, a mechanism that may facilitate tumor progression. Yan et al (17) reported that Gremlin1-overexpressing cells display increased growth and tumor formation abilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings should not be interpreted to conclude that cases of poor prognosis have a larger population of CSCs. Gremlin 1 was found to be secreted from stromal cancer-associated fibroblast (CAFs) in colon cancer and its expression was localized to invasion fronts (24)(25)(26). On the other hand, Gremlin 1 was found to be secreted by CSCs in glioblastoma and was thought to prevent CSCs from differentiating by antagonizing the effects ofBMPs (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…BMPs are members of the transforming growth factor (TGF)-β superfamily and play an essential role during development and differentiation while Gremlin 1 is also related to differentiation in combination with BMPs and its dysregulation results in developmental diseases (20)(21)(22)(23). Gremlin 1 is overexpressed in various types of human cancers (24)(25)(26). Recently several studies have demonstrated that CSCs prevent the BMP differentiating effect by secreting Gremlin 1 in glioblastoma, suggesting that Gremlin 1 plays a role in maintenance of CSC properties (27,28).…”
Section: Introductionmentioning
confidence: 99%